Vastus lateralis muscle architecture, quality, and stiffness are determinants of maximal performance in athletes? - Lanferdini, F. J.; Viera, H. L. S.; Gidiel-Machado, L.; Leite-Nunes, T. D.; Soldatelli, I. M.; Porporatti, L. B.; Matheus, S. C.; Lopes dos Santos, D.; Saccol, M. F.; Royes, L. F. F. (Journal of Biomechanics, 2025)
Understanding intrinsic muscular adaptations more deeply can help clarify their relationships with sports performance. Therefore, the aim of this study was to determine if vastus lateralis muscle architecture, quality and stiffness can explain knee extensor maximal torque and countermovement and squat jump performance of athletes. One hundred and two athletes were evaluated based on the architecture, quality and stiffness of the vastus lateralis at rest. Furthermore, the knee extensor maximal voluntary isometric contraction and maximal concentric contraction at 60°/s and vertical jumps countermovement and squat jump performance were measured. Stepwise linear regression showed vastus lateralis echo intensity and muscle thickness determine knee extensor maximal voluntary isometric contraction (r2 = 0.435) and knee extensor maximal concentric contraction at 60°/s (r2 = 0.400) in athletes. Moreover, vastus lateralis echo intensity, muscle thickness and pennation angle can determine athletes` performance during countermovement (r2 = 0.439-0.578) and squat-jump (r2 = 0.459-0.570). The findings emphasize that vastus lateralis muscle architecture and quality is an important determinant of maximal knee extensor torque (40-44 %) and countermovement (44-58 %) and squat-jump (46-57 %) performance. Our results demonstrate that the muscle architecture and quality of the vastus lateralis are important determinants of torque and power output performance across various sports disciplines.